1984
DOI: 10.1021/jm00374a017
|View full text |Cite
|
Sign up to set email alerts
|

Selective delivery of cytotoxic compounds to cells by the LDL pathway

Abstract: Cancer cells need cholesterol to make new membrane. They get it either by de novo synthesis or from low-density lipoprotein (LDL), or both. Some types of cancer have very high LDL requirements. LDL particles, which circulate in the blood, contain a cholesteryl ester core surrounded by a phospholipid coat containing apoproteins that are recognized by LDL receptors on cell surfaces. After attachment to cells, LDL is endocytosed into lysosomes, where the core is exposed and hydrolyzed. A technique is known whereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 12 publications
2
51
0
Order By: Relevance
“…Because of their hydrophobic core, the nLDLs are expected to provide a mechanism for the transport of hydrophobic drugs. In addition, hydrophilic drugs can be converted to hydrophobic pro-drugs by chemical modifications as suggested by several laboratories (Lundberg et al, 2003, Firestone et al, 1984, Dubowchik and Firestone, 1995 thus increasing the arsenal of drugs that can be potentially targeted to GBM via nLDL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their hydrophobic core, the nLDLs are expected to provide a mechanism for the transport of hydrophobic drugs. In addition, hydrophilic drugs can be converted to hydrophobic pro-drugs by chemical modifications as suggested by several laboratories (Lundberg et al, 2003, Firestone et al, 1984, Dubowchik and Firestone, 1995 thus increasing the arsenal of drugs that can be potentially targeted to GBM via nLDL.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously suggested that plasma-derived LDL could be used as a drug delivery system for tumors expressing LDLR since its hydrophobic core has the possibility of incorporating lipophilic drugs (Firestone, 1994, Rensen et al, 2001. Drugs have been either directly loaded onto plasma LDL or the core lipids of LDL were replaced with drugs (Callahan et al, 1999, Ji et al, 2002, Chu et al, 2001, Vitols et al, 1985, Firestone et al, 1984, Dubowchik and Firestone, 1995, Vitols et al, 1990. Plasma LDL, however, is less than ideal as a targeting agent since it is difficult to isolate in large quantities and is variable in composition and size.…”
Section: Introductionmentioning
confidence: 99%
“…Most lipoproteins can pass from the vascular system into the body tissues (13). Furthermore, it is now possible to sequester a variety of lipophilic drugs into lipoproteins (14)(15)(16)(17)(18)(19) '25I-labeled-acetyl-LDL ('25I-acetyl-LDL) was fractionated on a Sephadex G-15-120 column, dialyzed against buffer A, and filtered before use. Acetyl-LDL:MTP-PtdEtn Complex Formation.…”
mentioning
confidence: 99%
“…According to procedures by Firestone et al (27) and Cope and Ciganek (28), to a solution of 1.09 g (4.85 mmol) of 25, prepared according to the procedure of Wertheim (29), in 12 ml of dry CH 2 Cl 2 was added 1.3 ml (14.5 mmol) of (COCl) 2 and five drops of DMF. The mixture was stirred at 0ЊC for 2 h. The solvent was evaporated to give a light yellow solid, which was dissolved in 10 ml of dry ether.…”
Section: ␤-(4-benzoylbenzoyl)amino-cholest-5-ene (10)mentioning
confidence: 99%
“…A solution of 680 mg (1.9 mmol) of 3,5-dibromo-4-hydroxybenzophenone (27), mp 155-156ЊC, prepared by the method of Blakey, Jones, and Scarborough (30), and 61 mg (0.19 mmol) of tetrabutylammonium bromide in 2 ml of 2 M NaOH was treated with 365 mg (0.80 mmol) of 13 in 5 ml of EtOAc and heated at reflux for 4 days. The aqueous layer was removed and the EtOAc layer was washed with 2 ϫ 10 ml of water, dried, filtered, and evaporated to afford 1.1 g of residue, which was treated with 2 ϫ 10 ml of 1:4 EtOAc:hexane to precipitate excess 27 that was collected by filtration.…”
Section: ␣5-cyclo-22-(3ј5ј-dibromo-p-benzoylphenoxy)5␣-2324-bisnomentioning
confidence: 99%